(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
To ensure optimal performance and longevity of LED (light-emitting diode) downlights, it is crucial to address the associated thermal challenges. This study employs computational fluid dynamics (CFD) thermal simulation software to develop a comprehensive model of LED downlight heat dissipation. Various heat loads and material properties, including thermal conductivity, thermal resistance and thermal emissivity, are considered.The dissipation analysis integrates numerical modeling with laboratory data to provide a thorough evaluation of the lamp's thermal performance. The primary focus is on the dissipation effects of different quantities of LEDs and varying distances between LED rings. The aim is to enhance the dissipation efficiency of current LED downlight products by optimizing the light source arrangement.Experimental validation confirms that optimizing the light source arrangement significantly improves the operating temperatures of LEDs. This optimization is expected to substantially extend the lifespan of LED lights. The results offer valuable insights for designers and contribute to the understanding of thermal dynamics in LED downlights. By optimizing the light source architecture, designers can improve the overall reliability and lifespan of LED downlights by achieving more optimal operating temperatures.